Analisis Faktor Dan Dampak Penggunaan Bahasa Gaul Terhadap Keterampilan Berbahasa Indonesia Di Kalangan Mahasiswa - Sanas Tasia Sihaloho; Khairani Aprilia; Lili Tansliova (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Language is the soul of the nation, and also the identity of the nation. Language is also a communication tool in speaking that facilitates interaction. Humans can convey their ideas, notions and opinions through language. Over time, language also develops. The aim of this research is to find out the extent of the use of slang among students. And also the factors that cause slang and how it impacts language skills as well as the good and correct use of Indonesian. The research method used in this research is the qualitative method. Qualitative methods or data analysis methods are based on information or data obtained from previous research.